Stereotip gender lintas generasi: Eksplorasi konstruksi gender kontemporer generasi milenial (Y) dan generasi pascamilenial (Z) di Bandung - Hani Yulindrasari; Vina Adriany (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2023)
Millennials (Y), born between 1981-2000, and post-millennial (Z), born in 2000 and after, grew up in two very different socio-economic-political contexts. The Gen Ys were born and grew up in Soeharto's authoritarian era, and Gen Zs were born after the fall of Soeharto, but both grew up in the democratic era with the massive development of information technology. Both Millennials and post-millennials face different gender issues from previous generations. Even for similar gender issues, different context demands a different approach in understanding the issues. This research explores the construction of masculinity and femininity that is understood and believed by the Bandung’s millennials (Y) and post-millennials (Z) generation. Data collection was carried out in two stages. The first stage used the photo-interviewing method with 20 participants. The second stage was conducted with an online survey method of 184 respondents. The results show that millennial and post-millennial generations have an understanding of gender that tends to be non-stereotyping, not many signifiers are categorized as feminine or masculine.